Causes of stress in healthcare workers in hospital institutions - Keković Maja T.; Peličić Damir N.; Radević Svetlana R. (Srpsko lekarsko drustvo, 2022)
Introduction: Stress in healthcare workers in the hospital is a series of harmful physiological and psychological reactions to situations in which certain job requirements are not in line with its capabilities. Aim: The purpose of this study was to identify the presence of stress in health care workers in the hospital conditions of the Clinical Center of Montenegro in Podgorica. Material and Methods: A descriptive research method was chosen. The sample consisted of persons of both sexes. 113 randomly selected respondents participated in the research, the target group is respondents employed at the Clinical Center of Montenegro, the Institute of Pediatrics, of which 27% are doctors and 73% nurses-technicians, of different education. An anonymous survey questionnaire compiled for the purposes of this research was used as a research instrument. It includes the working population of nurses and doctors, aged 20 to 65. Results: Measuring stress levels in health workers 27 variables were identified as potential causes of stress. Respondents point out "inadequate personal income" (68.14%) as the major cause of stress. More than a half of the respondents (50.44 %), point out that the biggest cause of stress is "Work overload". In third place is "Misinformation of patients from the media and other sources" (46.02%). As with previous considerations, it is evident that different causes of stress are treated differently in relation to the organizational unit in which the employee performs work duties. Conclusion: The biggest causes of stress, and therefore psychosomatic illnesses, are fear, worry and guilt. Lack of time, work pressures, deadlines, high expectations, but also many other factors can affect the occurrence of stress. Precisely for the above reasons, and having in mind the nature of work, this research sought to contribute to measuring how certain stressors can affect employees in a health care institution.